Normal Liver Stiffness in Healthy Adults Assessed By Real-Time Shear Wave Elastography and Factors That Influence This Method - Huang, Zeping; Zheng, Jian; Zeng, Jie; Wang, Xiaoli; Wu, Tao; Zheng, Rongqin (Ultrasound in medicine & biology, 2014)
Real-time shear wave elastography (SWE) is a novel two-dimensional elastographic method that is used to estimate the severity of liver fibrosis. However, the normal range of liver stiffness (LS) and the possible factors that influence SWE are not well understood. The aims of the current study are to define the normal range of LS in healthy subjects and to explore the factors that may affect SWE. A total of 509 healthy subjects underwent SWE to determine the stiffness of their livers, and the effects of gender, age and body mass index (BMI) on LS were analyzed. The effects of different factors on SWE, including the testing position, measurement depth and size of the region of interest (ROI), were analyzed in 137 subjects. SWE imaging was successfully performed in 502 healthy subjects (98.6%, 502/509). The mean value of the SWE measurements in 502 individuals was 5.10 ± 1.02 kPa, and the 95% confidence interval was 5.02–5.19 kPa (range: 2.4–8.7 kPa). We found that the detective position within the liver had a significant impact on the liver stiffness measurement (LSM), and the lowest coefficient of variation (CV = 8%) was obtained for LSMs made at segment V. LS was greater at a depth >5 cm (5.78 ± 1.66 kPa) compared with depths ≤5 cm (4.66 ± 0.77 kPa, p < 0.001); LS was also greater in men than in women (5.45 ± 1.02 kPa vs. 4.89 ± 0.96 kPa, p < 0.001). However, there were no significant differences in the LS values regarding the size of the ROI, age or BMI (all p > 0.05). The mean LS value in all 502 healthy subjects was 5.10 ± 1.02 kPa. The mean LS value obtained by SWE was not influenced by the size of the ROI, age or BMI, but the mean value was significantly influenced by the different segments of the liver, the detection depth and gender.